Bidirectional relationship between Helicobacter pylori infection and nonalcoholic fatty liver disease: insights from a comprehensive meta-analysis - Zhang, Daya; Wang, Qi; Bai, Feihu (Frontiers in Nutrition, 2024)
Background: Helicobacter pylori (H. pylori) infection and nonalcoholic fatty liver disease (NAFLD) represent significant concerns in global health. However, the precise relationship between H. pylori and NAFLD remains a subject of ongoing debate. This study endeavors to elucidate the association between H. pylori infection and the susceptibility to NAFLD. Furthermore, we aim to investigate the interplay among H. pylori infection, NAFLD, and metabolic syndrome (MetS).We conducted an extensive search of the PubMed, EMBASE, and Web of Science databases spanning from inception to January 2024. Our examination focused on rigorous studies investigating the correlation between H. pylori infection and NAFLD. Utilizing a random-effects model, we computed the pooled odds ratio (OR) and corresponding 95% confidence interval (CI).Additionally, we assessed statistical heterogeneity, performed sensitivity analyses, and scrutinized the potential for publication bias.Results: Thirty-four studies involving 175,575 individuals were included in our meta-analysis. Among these, 14 studies (involving 94,950 patients) demonstrated a higher incidence of NAFLD in H. pylori infection-positive individuals compared to H. pylori infection-negative individuals [RR=1.17, 95%CI (1.10, 1.24), Z=4.897, P<0.001]. Seventeen studies (involving 74,928 patients) indicated a higher positive rate of H. pylori infection in patients with NAFLD compared to those without NAFLD [RR=1.13, 95%CI (1.02, 1.24), Z=2.395, P=0.017]. Sensitivity analyses confirmed the robustness of these findings, and funnel plot analysis revealed no significant publication bias. Furthermore, we observed associations between H. pylori infection or NAFLD and various metabolic factors, including body mass index (BMI), blood pressure, lipids, liver function, and kidney function.Our meta-analysis presents evidence supporting a reciprocal relationship between H. pylori infection and the susceptibility to NAFLD. Nevertheless, additional investigations are warranted to bolster this correlation and unravel the underlying mechanisms involved.